Occupational Choice and the Spirit of Capitalism* - Doepke, Matthias; Zilibotti, Fabrizio (Quarterly Journal of Economics, 2008)
The British Industrial Revolution triggered a socioeconomic transformation whereby the landowning aristocracy was replaced by industrial capitalists rising from the middle classes as the economically dominant group. We propose a theory of preference formation under financial market imperfections that can account for this pattern. Parents shape their children's preferences in response to economic incentives. Middle-class families in occupations requiring effort, skill, and experience develop patience and a work ethic, whereas upper-class families relying on rental income cultivate a refined taste for leisure. These class-specific attitudes, which are rooted in the nature of preindustrial professions, become key determinants of success once industrialization transforms the economic landscape.